2022
DOI: 10.3390/foods11071006
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of Consumers in the Prevention of Foodborne Diseases: An Ethnographic Study of Italian Families

Abstract: A high incidence of foodborne diseases occurs in the home setting because consumers adopt inappropriate preparation, consumption, and storage procedures. The present study applies an ethnographic approach to identify inadequate practices that could increase the incidence of foodborne diseases. Techniques related to the ethnographic approach were used: participant observation, kitchens mapping, collection of photographic material, and informal interviews in natural settings. A sample of 14 families was involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 75 publications
0
9
0
1
Order By: Relevance
“…Research has shown that a significant proportion of foodborne illnesses are caused by poor domestic food handling practices by consumers (Menini et al, 2022;Redmond and Griffith, 2003). Much of this literature has focused on the role of risk perceptions of consumers (Machado Nardi et al, 2020).…”
Section: The Psychology Of Food Safety Risks and Perceptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that a significant proportion of foodborne illnesses are caused by poor domestic food handling practices by consumers (Menini et al, 2022;Redmond and Griffith, 2003). Much of this literature has focused on the role of risk perceptions of consumers (Machado Nardi et al, 2020).…”
Section: The Psychology Of Food Safety Risks and Perceptionsmentioning
confidence: 99%
“…In their study of chicken preparation by consumers, Bergsma et al (2007, p. 554) found that "respondents felt they were in control of risks involved with chicken meat preparation." Yet, a considerable amount of foodborne illness is attributed to unsafe domestic food handling practices and preparation (Fischer et al, 2006;Lin et al, 2005;Menini et al, 2022). For instance, Redmond and Griffith (2004) found that consumers perceived that they have more control over food safety through their own preparations than other people have.…”
Section: Illusion Of Controlmentioning
confidence: 99%
“…However, the habit of buying raw milk from a local farmer may turn out to be a source of microbiological risks and reduced nutritional value. The participants in the study [ 21 ] demonstrated a lack of clear knowledge of how to treat raw milk, doing it “as it has always been done.” Raw milk must be boiled before consumption, because it can contain pathogens. However, the only correct treatment for milk is pasteurization, developed by the French chemist Louis Pasteur [ 22 ].…”
Section: Omnipresent Chemophobia and Its Consequencesmentioning
confidence: 99%
“…Similarly, there is a clear parallel between an aversion to chemistry and a disregard for microbiological risks. The same study [ 21 ] shows that participants who try to avoid dyes, preservatives and pesticides, simultaneously practice improper hand-washing, improper use of kitchen towels and sponges, improper washing of food (e.g., eggs, fruits, and vegetables) and utensils, uncontrolled presence of children and pets in the kitchen, and improper food storage—all factors that significantly increase the risk of microbiological contamination of food. Especially, alarming is the lack of hand-washing with detergents, which is observed for almost all participants.…”
Section: Omnipresent Chemophobia and Its Consequencesmentioning
confidence: 99%
“…Food microbiological contamination by food-borne pathogenic bacteria represents a critical concern to both consumers and the food industry worldwide [ 1 ]. Particularly, according to European guidelines 2021 European Center for Disease Control (ECDC)—European Food Safety Authority (EFSA) summary report on zoonoses, during 2019–2020, 8261 food-borne outbreaks involving 69,480 cases of illness, 5534 hospitalisations and 94 deaths were reported.…”
Section: Introductionmentioning
confidence: 99%